Preparation of Mesoporous SiO2 and ZnO•SiO2 Composite from Raw Rice Husk for Removal of Organic Dye - Le, Tien Dat; Hoang, Thi Thu; Nguyen, Thi Van; Vu, Anh Tuan (Old Journal, 2019)
Mesoporous SiO2 and ZnO•SiO2 composite (10 wt.% of SiO2) were prepared from rice husk for removal of organic dye (Janus Green B, JGB). As-prepared samples were characterized by XRD, FE-SEM, FT-IR, and N2 adsorption/desorption isotherms. SiO2 was observed as mesoporous material with large surface area (98.2 m2/g) and high pore volume (0.746 cm3/g). However, these values were significantly decreased when ZnO doped in ZnO•SiO2 composite. The performance of SiO2 was evaluated by adsorption of JGB and performance of ZnO•SiO2 composite was evaluated by photo-degradation of JGB under low UV intensity (8 W). The adsorption capacity of SiO2 was 3379.5 mg/g and adsorption rate was 0.062 min-1. The degradation efficiency of JGB on ZnO•SiO2 composite was 97.9% in 60 min and degradation rate was 0.061 min-1.